Strengthening Rural MSME Digital Marketing Literacy through Practical Training in Kalipancur Village - Wenti Ayu Sunarjo; Siti Nurhayati; Suryani Tri Suci; Widunaini (PT. Berkah Digital Teknologi, 2026)
This community service program aimed to strengthen the initial digital marketing literacy and practical readiness of rural micro, small, and medium enterprise (MSME) actors in Kalipancur Village, Bojong District, Pekalongan Regency. The activity was conducted on 23 May 2026 at the Kalipancur Village Hall through a community-development approach. The intervention combined an introductory seminar, demonstrations, guided discussion, and initial facilitation on WhatsApp Business, Instagram, TikTok, marketplaces, product photography, content planning, and the use of Canva and CapCut. Program evaluation relied on descriptive qualitative evidence from implementation observations, participant questions, reported constraints, and immediate responses after the session. No formal pretest-posttest, verified attendance profile, or post-program sales monitoring was available; therefore, the article does not claim increased turnover. Participant interaction indicated improved awareness of the relevance of digital visibility and a clearer understanding of low-cost steps for beginning online promotion. Several participants reportedly started activating WhatsApp Business and searching Instagram and TikTok for content references. Persistent barriers included limited content-creation skills, time constraints, low confidence, and the perception that rural businesses depend only on nearby customers. The program contributed primarily to early-stage digital readiness. Sustainable results require repeated hands-on mentoring, competency-based evaluation, verified participant documentation, and follow-up measurement using account analytics and sales indicators